EFEKTIVITAS PROGRAM KELAS BENSI ( KELUARGA SEHAT BEBAS HIPERTENSI) TERHADAP MANAJEMEN HIPERTENSI - Sri Wahyuni Adriani; Yulanda irma Tiara; Rias Elia Rahmad; Linda Putri Mahardika; Nur Fikriyah; Muhammad Imadduddin A (Jurnal Ilmu Keperawatan Komunitas, 2021)
Background: Hypertension is a degenerative disease that is a major problem in the community. This disease is often called the silent killer because it has no symptoms. This study aims to analyze the effectiveness of the “Bensi Class” program on efforts to improve hypertension management in the Gumukmas, Puger and Lumajang areas. This intervention is different from other studies, other studies use lecture and booklet methods while "Class Bensi" combines lecture methods, hypertension exercise, cucumber juice so that family members are able to monitor family members' blood pressure. Methods: The study design used a quasi-experimental with pretest-posttest design with control group. Sample of 30 family members with hypertension. This research was conducted in November 2020, using a Likert scale instrument quesioner. The data was analized using Independent T-Test with a value of 0.05. Results: The results showed the three aspects of knowledge, attitude and behavior after intervention was obtained with a p value of 0.0005. Conclusion: The Bensi class program is effective to improve hypertension management in hypertensive patients. Discussion: Management of hypertension applied by family members can be carried out on an ongoing basis if the family understands the hypertension information that has been given.